Camostat Mesylate Versus Lopinavir/Ritonavir in Hospitalized Patients With COVID-19—Results From a Randomized, Controlled, Open Label, Platform Trial (ACOVACT) - M. Karolyi; E. Pawelka; S. Omid; F. Koenig; V. Kauer; B. Rumpf; W. Hoepler; A. Kuran; H. Laferl; T. Seitz; M. Traugott; V. Rathkolb; et al. (Frontiers in Pharmacology, 2022)
Background: To date, no oral antiviral drug has proven to be beneficial in hospitalized patients with COVID-19.Methods: In this randomized, controlled, open-label, platform trial, we randomly assigned patients ≥18 years hospitalized with COVID-19 pneumonia to receive either camostat mesylate (CM) (considered standard-of-care) or lopinavir/ritonavir (LPV/RTV). The primary endpoint was time to sustained clinical improvement (≥48 h) of at least one point on the 7-category WHO scale. Secondary endpoints included length of stay (LOS), need for mechanical ventilation (MV) or death, and 29-day mortality.Results: 201 patients were included in the study (101 CM and 100 LPV/RTV) between 20 April 2020 and 14 May 2021. Mean age was 58.7 years, and 67% were male. The median time from symptom onset to randomization was 7 days (IQR 5–9). Patients in the CM group had a significantly shorter time to sustained clinical improvement (HR = 0.67, 95%-CI 0.49–0.90; 9 vs. 11 days, p = 0.008) and demonstrated less progression to MV or death [6/101 (5.9%) vs. 15/100 (15%), p = 0.036] and a shorter LOS (12 vs. 14 days, p = 0.023). A statistically nonsignificant trend toward a lower 29-day mortality in the CM group than the LPV/RTV group [2/101 (2%) vs. 7/100 (7%), p = 0.089] was observed.Conclusion: In patients hospitalized for COVID-19, the use of CM was associated with shorter time to clinical improvement, reduced need for MV or death, and shorter LOS than the use of LPV/RTV. Furthermore, research is needed to confirm the efficacy of CM in larger placebo-controlled trials.Systematic Review Registration: [https://clinicaltrials.gov/ct2/show/NCT04351724, https://www.clinicaltrialsregister.eu/ctr-search/trial/2020-001302-30/AT], identifier [NCT04351724, EUDRACT-NR: 2020–001302-30].